The global sustainability footprint of sovereign wealth funds - LIANG, Hao (Institutional Knowledge at Singapore Management University, 2020)
With the emergence of sovereign wealth funds (SWFs) around the world managing equity of over $8 trillion, their impact on the corporate landscape and social welfare is being scrutinized. This study investigates whether and how SWFs incorporate environmental, social, and governance (ESG) considerations in their investment decisions in publicly listed corporations, as well as the subsequent evolution of target firms' ESG performance. We find that SWF funds do consider the level of past ESG performance as well as recent ESG score improvement when taking ownership stakes in listed companies. These results are driven by the SWF funds that do have an explicit or implicit ESG policy and are most transparent, and by SWF originating from developed countries and countries with civil law origins. In relation to engagement, we find by means of two natural experiments with exogenous shocks (the Deepwater Horizon catastrophe and Volkwagen diesel scandal) that the ESG scores do not change significantly more for firms in which SWFs have ownership stakes. This potentially suggests that SWFs in general do not actively steer their target firms towards higher levels of ESG.